DEVELOPMENT OF A COORDINATION METHOD FOR EFFECTIVE DECISION-MAKING IN A HIERARCHICAL MULTILEVEL INDUSTRIAL SYSTEM - Bayas, M. M. (Radio Electronics, Computer Science, Control, 2014)
In modern conditions of manufacturing the ever increasing size of enterprises leads to objective changes in the interdependence of their subordinated structures. The resulting complexity requires modernization of the process management systems. One important direction task in this modernization is the development of effective methods of coordination. Therefore, this article addresses the problem of coordination in decision making among a group of autonomous production units. The object of study is the local decision making process on a dairy plant, which operate with three production lines. The subject of study is the coordination of operations when there is only one packaging machine. The objective of this work is to increase the overall effectiveness index of a system of production units by means of optimal resource allocation and synchronization of operations of technological processes. For effective coordination it is proposed a method that ensures the optimization of processes while considering the particular preferences of each local decision-making unit. For each subordinated decision unit or coordinator, an objective function measures the effectiveness of the subprocesses activities. The coordinator affects the lower-level decision-making so that the performance of the whole system is optimized. It incorporates a hierarchical multilevel system for the management of activities, and the detailed mathematical modeling of the sequencing of operations. The method proposed is based on the theory of fuzzy sets and fuzzy logic. The decision-making process is accomplished by a minimax estimation of the membership functions. The coordinated operations give as result a higher global effectiveness. Additionally, for the comparison of preferences, the normalized criteria of effectiveness based on the technological characteristics of each process are suggested.